Shaping Art with Art: Morphological Analysis for Investigating Artistic Reproductions. - Bell, Peter; Ommer, Björn; Monroy Kuhn, Juan Antonio (Computer Vision – ECCV 2012. Workshops and Demonstrations., 2012)
Whereas one part of art history is a history of inventions, the other part is a history of transfer, of variations and copies. Art history wants to understand the differences between these, in order to learn about artistic choices and stylistic variations. In this paper we develop a method that can detect variations between artworks and their reproductions, in particular deformations in shape. Specifically, we present a novel algorithm which automatically finds regions which share the same transformation between original and its reproduction. We do this by minimizing an energy function which measures the distortion between local transformations of the shape. Thereby, the grouping and registration problem are addressed jointly and model complexity is obtained using a stability analysis. Moreover, our method allows art historians to evaluate the exactness of a copy by identifying which contours where considered relevant to copy. The proposed shape-based approach thus helps to investigate art through the art of reproduction.<br
Keywords: Transformation Model; Thin Plate Spline; Local Transformation; Landmark Point; Contour Extraction